PENJATUHAN SANKSI PIDANA TERHADAP ANAK PELAKU KEJAHATAN - Pranggi Siagian; Alvi Syahrin; Mahmud Mulyadi; Marlina Marlina (Universitas Sumatera Utara, 2015)
ABSTRACT Sanctions provided judges against juvenile offenders is in the form of sanctions measures and sanctions in prison, but within 30 (thirty) decision of the district court examined, the judges are more likely to sanction a prison, whereas criminal sanctions contrary to Child Protection Law. Of 30 (thirty) cases studied judge gives legal considerations through legal facts, facts trial, judgment based on a minimum of two (2) valid evidence, along with confidence, asking the opinion of the Board of Corrections and parents of children , and takes into account aggravating elements as a result of the defendant and the defendant relieve elements. The basic consideration in decisions to judges of juvenile offenders see in terms of the elements of the article have been met and other considerations is that such action can cause public unrest, as well as the obligations of judges in the decision to consider a report on the research community and the opinion of parents, as well as facts law and the facts in the trial are revealed, plus juridical considerations, this will give an overview to for the judge to make a decision that is fair.